تأثير السماد العضوي ( الغنمي والأخضر ) في نمو محصول القطن وانتاجيته - عبد العزيز محمد; جراد سمير; علي بسام (Latakia University Journal -Biological Sciences Series, 2019)
نفذ البحث خلال الموسميين الزراعيين 2009 – 2010 في محافظة الحسكة منطقة عامودا لدراسة تأثير السماد العضوي الغنمي بمعدل 30 طن / هـ وأربعة أنواع من السماد العضوي الأخضر ( عدس، بيقية، فول، شعير ) في نمو محصول القطن وانتاجيته مقارنة مع السماد الكيميائي (400 كغ يوريا، 83 كغ P2O5، 25 كغ K2O / هـ) . بينت الدراسة : تفوق التسميد بمخلفات الأغنام معنويا في زيادة طول الساق وعدد الفروع الخضرية والثمرية وعدد الجوزات، ووزن الجوزة وانتاجية القطن المحبوب مقارنة مع بقية أنواع الأسمدة المدروسة، ووصلت الزيادة في الانتاجية إلى ( 162.28 ) كغ / هـ بالمتوسط عند مقارنته مع السماد الكيميائي، ولم يتفوق السماد الكيميائي معنويا على محصول العدس المستخدم كسماد أخضر في طول الساق وعدد الفروع الخضرية ووزن الجوزة، وأثرت جميع المحاصيل البقولية المستخدمة كسماد أخضر في زيادة إنتاجية القطن المحبوب مقارنة مع المحصول النجيلي(شعير ) ومع الشاهد بدون تسميد وبزيادة بلغت(1715.14 ،1556.70 ،1350.46 ) كغ/هـ بالمتوسط عند استخدام ( عدس، بيقية، فول ) على التوالي خلال موسمي البحث . The reasearch was carried out during 2009 – 2010 in Al – Hasaka – Amoda - to study the effect of cattle manure at the rate of 30 ton / ha, and four organic green fertilizers ( Lentil, Vetch, Faba bean and Barely ) on the growth and productivityof cotton crop compared with chemical fertilizer 400 kg / ha urea, 83 kg / ha P2O5 and 25 kg / ha K2O . The cattle manure has some kind of superiority in terms of increased plant height, number of monopodia and sympodia branches, number of bolls, boll weight and the seed cotton productivitycompared with other fertilizers. The increase in the seed cotton productivity reached (162.28 ) kg / ha as average when compared with chemical fertilizer . The chemical fertilizer did not affect significantly on plant height, number of monopodia branches and boll weigt when compared with the legume crop ( Lentil ) . All legume crops which are used as green manure have significantly increased the seed cotton productivitycompared with Barely and the control without using any fertilizer(1715.14, 1556.70, 1350.46)kg / ha when using (Lentil, Vetch, Faba bean)during the two seasons of the research respectively.